Designing digital conversational agents for youth with multiple mental health conditions: Insights on key features from a youth-engaged qualitative descriptive study - Jingyi Hou; Jamie Gibson; Thalia Phi; Brian Ritchie; Louise Gallagher; Gillian Strudwick; George Foussias; Darren B Courtney; Aristotle Voineskos; Stephanie Ameis; Kristin Cleverley; Lisa D Hawke (Digital Health)
Objective This qualitative study aims to examine the key features and design elements of a mental health digital conversational agent (“Digital Conversational Agent” or “DCA”) for youth with multiple mental health conditions. Methods Twenty-eight youth participants aged 14 to 25 were recruited from the Toronto Adolescent and Youth (TAY) Cohort study. Data were collected through focus groups guided by a semi-structured interview guide. Focus group discussions were audio-recorded, and transcripts were analyzed using codebook thematic analysis. Youth engagement was integrated throughout the study. Results Four key themes were generated from the focus group data: (1) the importance of a customizable and flexible design for personalization; (2) confidentiality, privacy features and risk mitigation features; (3) the need for reliable, informative content that is user tested and validated; (4) a friendly and human-like interaction style. Conclusions The study identified key design features that may enhance youth engagement and trust in DCAs for mental health support. Collaborating with youth engagement specialist and industry partners underscored the value of co-designed approach in preparing to develop relevant, feasible, and ethical DCAs.